PENGARUH MOTIVASI, PERSEPSI RISIKO, PENGETAHUAN TERHADAP INVESTASI PADA UMKM MELALUI PLATFORM SECURITIES CROWDFUNDING - Naldi, Gio Alpri; Muljaningsih, Sri (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
This study aims to determine the effect of motivational variables, risk perception, knowledge on investment in MSMEs through the sharia securities crowdfunding platform. This study uses a quantitative approach with multiple linear regression analysis method. The sampling method is Non-Probability Sampling with Purposive Sampling Technique, and the number of samples is 30 respondents of sharia securities crowdfunding investors. The results of this study indicate that the variables of motivation, risk perception, knowledge have a simultaneous effect on investors in investing in MSMEs through the SCF Syariah platform. Meanwhile, the Risk Perception variable has a negative and insignificant effect on investors in investing in MSMEs through the SCF Syariah platform.